The Navajo - Stan, Susan; Lazzarino, Luciano (Vero Beach, Fla. : Rourke Publications, 1989)
Examines the history, traditional lifestyle, and current situation of the Navajo Indians.
Includes index.
School Library Journal.
6.0
5-8
Keywords: Navajo Indians -- Juvenile literature; Navajo Indians; Indigenous people of North America -- Juvenile fiction; Navajo Indians; Native Americans -- Southwestern States; Navajo Indians; Indigenous people of North America -- Juvenile fiction